Performance Assessment of University Lecturers: A Data Mining Approach - Milkhatun Milkhatun; Alfi Ari Fakhrur Rizal; Ni Wayan Wiwin Asthiningsih; Asslia Johar Latipah (Department of Informatics, Universitas Muhammadiyah Surakarta, Indonesia, 2020)
A lecturer with a good performance has a positive impact on the quality of teaching and learning. The said quality includes the delivery of teaching materials, learning methods, and ultimately the academic results of students. Performance of lecturers contributes significantly to the quality of research and community service which in turn improves the quality of teaching materials. It is desirable, therefore, to have a method to measure the performance of lecturers in carrying out the Tri Dharma (or the three responsibility) activities, which consist of teaching and learning process, research, and community service activities, including publications at both national and international level. This study seeks to measure the performance of lecturers and cluster them into three categories, namely